PENGARUH GCG, STRUKTUR MODAL, DAN CAPITAL EXPENDITURE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2018 – 2022 - Nugroho, Laurensia Shirley; Dyah Ayu, Stephana (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the influence of independent board of commissioners, institutional ownership, audit committee, capital structure, and capital expenditure on company value. This research was conducted on transportation companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2022 using the purposive sampling method. The number of samples in this study was 67 transportation companies. The sampling technique in this study used the purposive sampling method, where the sample in this study was 24 companies with a total of 67 observations. The methods used in this study are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination (R2). Based on the results of this study, it shows that: (1) The independent board of commissioners has a significant positive influence on the value of the company. (2) Institutional ownership has a significant positive effect on the value of the company. (3) The Audit Committee has a significant positive effect on the value of the company. (4) Capital structure has a significant negative effect on the value of the company. (5) Capital expenditure has a significant negative effect on the value of the company.